Good morning, p.b. bear! - Davis, Lee (Family Learning Orlando, Fla., 1998)
a charming children's story featuring P.B. Bear as he wakes up to a new day. As he stretches and gets ready, readers are taken through his morning routine, filled with delightful activities like breakfast and getting dressed. The story emphasizes the warmth of morning rituals and the simple joys of everyday life. With colorful illustrations and a gentle narrative, it invites young readers to join P.B. Bear in celebrating the little moments that make mornings special. Perfect for preschoolers, it encourages a positive start to the day!